2018
DOI: 10.1111/dech.12447
|View full text |Cite
|
Sign up to set email alerts
|

The Micropolitics of Dispossession and Resistance: Case Study of a Proposed Dam in Central India

Abstract: This article presents a study of the micropolitics of dispossession for a proposed medium‐sized irrigation project in an Adivasi region of Central India. The article explores the complex micropolitics of dispossession and collective action in the project planning stage, long before the formal processes of land acquisition actually begin. It highlights the importance of training the researchers’ gaze on the functioning of the local state in the pre‐acquisition phase. It shows how the local state uses various po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Earlier research conducted in the field of conservation-induced displacement in India mostly focussed on the immediate implications of displacement, barring a few exceptions where researchers have maintained a long-term engagement with displacement geographies and their micropolitics (Kabra and Mahalwal 2019). Given the 15-year gap between the evictions and this research, our study seeks to further understand the long-term implications of unplanned evictions and highlights the socioecological complexities of pastoral evictions in Indian Himalaya.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research conducted in the field of conservation-induced displacement in India mostly focussed on the immediate implications of displacement, barring a few exceptions where researchers have maintained a long-term engagement with displacement geographies and their micropolitics (Kabra and Mahalwal 2019). Given the 15-year gap between the evictions and this research, our study seeks to further understand the long-term implications of unplanned evictions and highlights the socioecological complexities of pastoral evictions in Indian Himalaya.…”
Section: Discussionmentioning
confidence: 99%
“…Only two case studies involving industrialisation were found, both centring around China for the same reasons driving urbanisation: the first case focused on China as an investor in Mauritius to acquire land for promoting the special economic zone model abroad [66]; and the second one was a domestic case of a county in Jiangxi Province in the central south region of China being used to obtain land for industry park development [67]. Only one case study examined a land grabbing conflict caused by a dam development project in Madhya Pradesh, India [68], despite debates on mega-infrastructure heating up globally.…”
Section: Geographic Distribution and Commonly Referenced Topicsmentioning
confidence: 99%
“…The continuing process of land acquisition for different infrastructure projects has witnessed enormous people’s resistance in different parts of India (See, Bosshard, 2011; Huber & Joshi 2017; Kabra & Mahalwal, 2018; Kipgen, 2017; Oskarsson, 2017). The resistance to large-scale dams are not merely an opposition to the promised benefits of the project; instead, it is standing against the social, economic and environmental cost it involves.…”
Section: The Indian Practice Of Displacement Resettlement and Rehabimentioning
confidence: 99%